2021
DOI: 10.1038/s41598-021-94318-x
|View full text |Cite
|
Sign up to set email alerts
|

Association of self-rated health with chronic disease, mental health symptom and social relationship in older people

Abstract: Chronic disease, mental health symptoms and poor social relations are reported common causes for poor self-rated health in older people. To assess the co-occurrence rate of chronic diseases, poor mental health and poor social relationships in older people, and determine their association with self-rated health. 6,551 older people in Zhongshan, China, participated a large health surveillance program were randomly selected and questioned about their SRH, chronic conditions, mental health symptoms and social rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 26 publications
6
25
0
Order By: Relevance
“…It was further revealed that older adults with poor SRH had high odds of reporting hypertension and diabetes, which is in line with the existing literature ( Noh et al, 2019 ; Wennberg et al, 2013 ; Yang et al, 2021 ). Older adults from higher economic background had a higher likelihood of hypertension and diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…It was further revealed that older adults with poor SRH had high odds of reporting hypertension and diabetes, which is in line with the existing literature ( Noh et al, 2019 ; Wennberg et al, 2013 ; Yang et al, 2021 ). Older adults from higher economic background had a higher likelihood of hypertension and diabetes.…”
Section: Discussionsupporting
confidence: 89%
“…Multimorbid adult patients have to struggle with many oral conditions that very often influence many aspects of their lives. It is crucial to know the exact problem of the patients diagnosed with common chronic diseases to be able to improve their quality of life [ 1 , 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multimorbidity affects patients’ social relations and mental health [ 2 ]. It is still a challenge to implement a healthy lifestyle and a strategy that would be helpful in reducing the effects of chronic diseases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that the rate of anxiety was 71.2%, the rate of depression was 64.7%, and the rate of somatic complaints was 64.9% [11]. However, the prevalence of somatic symptoms in China, especially in patients who were present at clinics or general hospitals, has not been well studied, and little attention has been given to the correlation of somatic symptoms with young and middleaged long-term hospitalized patients with mental illnesses [12]. erefore, we conducted a two-year survey over the somatic symptoms of patients with chronic mental illness who had stayed in the hospital for five years or more to investigate the status of the somatic symptoms in young and middle-aged psychiatric patients in long-term hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…A study showed that the rate of anxiety was 71.2%, the rate of depression was 64.7%, and the rate of somatic complaints was 64.9% [ 11 ]. However, the prevalence of somatic symptoms in China, especially in patients who were present at clinics or general hospitals, has not been well studied, and little attention has been given to the correlation of somatic symptoms with young and middle-aged long-term hospitalized patients with mental illnesses [ 12 ].…”
Section: Introductionmentioning
confidence: 99%